Recent progress on the detection of animal-derived food stimulants using mass spectrometry-based techniques - Zhang, Qiang; Du, Hongying; Zhang, Yingjian (Frontiers in Nutrition, 2023)
The misuse of animal-derived stimulants in food is becoming increasingly common, and mass spectrometry (MS) is used extensively for their detection and analysis. There is a growing demand for abused-substances detection, highlighting the need for systematic studies on the advantages of MS-based methods in detecting animal-derived stimulants.We reviewed the application of chromatography-mass spectrometry to the screening and detection of food stimulants of animal origin. Specifically, we analyzed four common animal sources of synthetic steroids, β-receptor agonists, zearalenol, and glucocorticoids. We also explored the potential of using chromatography-mass spectrometry to detect and analyze animal-derived foods.We searched and screened the Web of Science and Google Scholar databases until April 2023. Our inclusion criteria included a publication year within the last five years, publication language of English, and the research fields of food analysis, environmental chemistry, and polymer science. Although traditional techniques such as thin-layer chromatography and enzyme-linked immunoassays are simple, fast, and suitable for the initial screening of bulk products, they are limited by their relatively high detection limits. Among the methods based on MS, gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry are the most widely used for detecting food doping agents of animal origin. However, a sensitive method with high repeatability and a short analysis time for a large number of samples is still required. Advances in MS have enabled the detection of extremely low concentrations of these substances. Combining different techniques, such as high-resolution mass spectrometry, ultra-high performance liquid chromatography-tandem mass spectrometry, gas chromatography-combustion-isotope ratio mass spectrometry, ultra-high performance liquid chromatography-high resolution mass spectrometry, and two-dimensional chromatography, offers significant advantages for detecting trace illicit drugs in animal-derived foods. Due to advances in assay technology and sample preparation methods, sample collection and storage methods such as dried blood spots, dried urine spots, and volumetric absorptive microsampling are increasingly accepted because of their increased stability and costeffectiveness.MS significantly improves the efficiency of detecting doping agents of animal origin. With the continuous development of MS technology, its application in the fields of doping detection and the analysis of doping agents of animal origin is expected to become more extensive.